Antibody techniques - Malik, Vedpal S.; Lillehoj, Erik P. (Academic Press, 1994)
The applicability of immunotechniques to a wide variety of research problems in many areas of biology and chemistry has expanded dramatically over the last two decades ever since the introduction of monoclonal antibodies and sophisticated immunosorbent techniques. Exquisitely specific antibody molecules provide means of separation, quantitative and qualitative analysis, and localization useful to anyone doing biological or biochemical research. This practical guide to immunotechniques is especially designed to be easily understood by people with little practical experience using antibodies. It clearly presents detailed, easy-to-follow, step-by-step methods for the widely used techniques that exploit the unique properties of antibodies and will help researchers use antibodies to their maximum advantage.